About Some Edible Plants Distributed in the Fergana Valley - Zamira Yu. Jurayeva; Khusanboy E. Yuldashev; Ergashali Yu. Ruzmatov; Oygul Shirinova (Zien Journals, 2023)
This article contains information on the families, species and their importance in industry, as well as their bioecological characteristics, found in the Fergana Valley.
Keywords: morphobiological; rare; raw material